Context and Implications Document for: How child‐centred education favours some learners more than others. Issue 3 (18th October 2018) - Power, Sally; Rhys, Mirain; Taylor, Chris; Waldron, Sam
Abstract : This guide accompanies the following article: Power, S., Rhys, M., Taylor, C. & Waldron, S. How child‐centred education favours some learners more than others, Review of Education https://doi.org/10.1002/rev3.3137 .